The Differences on Students’ Learning Outcomes in Grade X at SMA Negeri 1 Parigi Through the Number Head Together (NHT) Learning Strategies and Discussion on the Topic of Redox Reaction - H.J, Nur Rahmadana Safitri; Diah, Anang Wahid M; Afadil, Afadil (Universitas Tadulako, 2019)
This study aimed to determine the differences in students’ learning outcomes in grade X at SMA Negeri 1 Parigi through of number head together (NHT) strategies and discussion on the topic of Redox Reaction. Type of this study was a quasi experiment with posttest-only control group design. This study was conducted in two groups namely Class X MIPA A as the experimental group (n = 35) and Class X MIPA B as the control group (n = 37). The students’ learning outcomes data were tested by using non-parametric statistical analysis Mann-Whitney U-test. The result showed that for the mean value of the experimental class was bigger than the control class that was 44.24 ˃ 29.18. The result of statistical analysis obtained Sig. 2-tailed (0.002) ˂ 0.05 and Zaccount (-3.069) ˂ Ztable (-1.96). The average score of the experimental class was 64.52 while the control class was 62. It can be concluded that there is a difference on students’ learning outcomes in grade X at SMA Negeri 1 Parigi through of NHT strategies and discussion method on the topic of redox reaction.